Poder Executivo e parlamentares: o caso do Ceará - Machado Neto, Francisco Edilberto Menezes (2010)
The Brazilian Political Science presents an interesting debate around the concept of “Presidencialismo de coalizão” (coalition presidentialism). Concept emerged in the late 1980's to describe the institutional organization of Brazil, he is the subject of intense debate among scholars. On the one hand, researchers argue that the Brazilian presidentialism, by nature, is weak and based on agreements whose role reserved for party institutions is very small. In another position, some researchers argue that the institutional structure of Brazil is strong, has a clear role and is comparable to their European counterparts. A third possibility also proposes an intermediate view between the two, arguing that the presidential system in Brazil is now showing strong, sometimes weak. From this scenario, I investigate the positions involved in the debate, focusing on the benches and example of Ceará Federal Representatives. In addition to library research, interviews and data collected at sites comprised the field material, focusing mainly on data relating to elections to the period 1986- 2006, the distribution observed in partisan political stands of different compositions during this period and the individual amendments proposed by parliamentarians. Although not yet addressed by the current literature in depth, the coalition presidentialism has political aspects with local conjuncture that deserve to be unraveled. Not only the national stage appears to be relevant to think the parliamentary support, but state and local questions impose themselves also as a powerful source of influence on the work of parliamentarians from Ceará.